CONTEMPORARY CRITICAL CRIMINOLOGY - DeKeseredy, Walter S., 1959- ([S.l.] : ROUTLEDGE, 2021)
The concept of critical criminology - that crime and the present-day processes of criminalization are rooted in the core structures of society - is of more relevance today than it has been at any other time. Written by an internationally renowned scholar, Contemporary Critical Criminology introduces the most up-to-date empirical, theoretical, and political contributions made by critical criminologists around the world. In its exploration of this material, the book also challenges the erroneous but widely held notion that the critical criminological project is restricted to mechanically applying theories to substantive topics, or to simply calling for radical political, economic, cultural, and social transformations. Now fully updated and expanded in a new edition, this book offers further coverage of new directions in critical criminology, covering topics such as: Green criminology Indigenous criminology Intersectionality Narrative criminology Rural critical criminology Queer criminology Zemiology Critical research methods Contemporary critical criminological policies Written in a clear and direct style, this book is an essential source of reference for both undergraduate and postgraduate students of criminology, deviance and social control, criminological theory, social policy, research methodology, and criminal justice.
OCLC-licensed vendor bibliographic record.
Keywords: Critical criminology; Criminology; SOCIAL SCIENCE / Criminology; SOCIAL SCIENCE / Penology; SOCIAL SCIENCE / Violence in Society